The Influence of Transformational Leadership and Interpersonal Communication on Teachers’ Performance - Ade Melianah; Matin Matin; Heru Santosa (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research intends to observe how transformational leadership and interpersonal communication affect teachers’ performance at the State Vocational High School of East Jakarta II. Researchers use the survey to collect quantitative data and multiple regression. Using the Slovin technique and closed-questionnaire, the researcher got 78 teachers of 353 people to become the research sample. The hypothesis is obtained from the t-test and F-test. The result shows that transformational leadership and teachers’ performance have a positive and significant effect, which means that the principals’ roles substantially improve teachers’ performance. Interpersonal communication and teachers’ performance also have positive and significant effects. It means that communication between principal and teachers’ can have a significant impact on teachers’ performance. Transformational leadership and interpersonal communication have a positive and significant effect with a coefficient of determination of 0.205 or 20.5%, meaning that transformational leadership and interpersonal communication contribute to an increase in teacher performance of 20.5%.